Efektivitas Media Flash Card untuk meningkatkan Konsep Diri Siswa - Farid, Dimas Ardika Miftah; Wirastania, Aniek; Hartanti, Jahju (Universitas Nusantara PGRI Kediri, 2024)
The objective of this study is to examine the effectiveness of flashcards in enhancing students' self-concept. Self-concept is described as an individual's ability and characteristics that influence how they think about themselves and how they wish to present themselves ideally. This research employs a pre-experimental design using a one-group pre-test and post-test design. Data collection was conducted at Junior High School (SMP) Jalan Jawa Surabaya. Based on observations and interviews, it was found that approximately 55% of students face low self-concept issues, as indicated by the completion of guidance and counseling instruments. The statistical test results showed an Asymp. Sig value of 0.036, where Asymp. Sig 0.001 < α = 0.05, leading to the rejection of Ho and acceptance of H1. The pre-test and post-test scores also demonstrated an improvement in students' self-concept after the intervention with flash cards. Therefore, it can be concluded that flashcards are effective in enhancing students' self-concept.